1997
DOI: 10.1073/pnas.94.21.11490
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of interferon γ-activated STAT1 by UV light

Abstract: STAT1 is a cytoplasmic transcription factor that is phosphorylated by Janus kinases (Jak) in response to interferon-␥ (IFN␥). Phosphorylated STAT1 translocates to the nucleus, where it turns on specific sets of IFN␥-inducible genes. Here, we show that UV light interferes with tyrosine phosphorylation of STAT1, thereby hindering IFN␥ from exerting its biological effects. This effect is not due to a down-regulation of the IFN␥ receptor because phosphorylation of upstream-located Jak1 and Jak2 was not suppressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 40 publications
3
50
0
1
Order By: Relevance
“…Along this line, STAT3 phosphorylation, which also appears to be involved in IL-2 signaling, was not significantly affected by UV (data not shown). In this context it is important to mention that it was previously observed that IL-6-mediated phosphorylation of STAT3 was also not inhibited by UV (15). These findings and the fact that UV is a well known activator of nuclear factor-B and AP-1 both in vitro and in vivo (39 -41) .…”
Section: Suppression Of Il-2-induced Activation Of Stat5 By Uv Is Prementioning
confidence: 76%
See 1 more Smart Citation
“…Along this line, STAT3 phosphorylation, which also appears to be involved in IL-2 signaling, was not significantly affected by UV (data not shown). In this context it is important to mention that it was previously observed that IL-6-mediated phosphorylation of STAT3 was also not inhibited by UV (15). These findings and the fact that UV is a well known activator of nuclear factor-B and AP-1 both in vitro and in vivo (39 -41) .…”
Section: Suppression Of Il-2-induced Activation Of Stat5 By Uv Is Prementioning
confidence: 76%
“…Phosphorylated STAT1 dimerizes, translocates to the nucleus where it binds to the IFN␥-activated sequences (GAS) in various promoters, and ultimately induces specific gene transcription. We observed that UV inhibits IFN␥-induced STAT1 phosphorylation and consequently STAT1 binding capacities (15). Because phosphorylation of STAT1 is a critical event in IFN␥ signaling, UV inhibits IFN␥ from exerting its biological effects via this mechanism.…”
mentioning
confidence: 74%
“…We used anisomycin as stress stimulus for MEFs instead of LPS, because the expression of some essential components of the LPS signaling pathway is restricted to hematopoietic cells (26). We also ruled out UV light as inducer, because it has been shown that this stimulus down-regulates IFN-␥-induced Tyr-701 phosphorylation of STAT1 by unknown mechanisms (27).…”
Section: Ifn-␥-stimulated Expression Of the Stat1 Target Gene Irf1 Domentioning
confidence: 99%
“…It interferes with Th1 type cytokine production, such as IFN-γ and IL-7, and their signaling pathways on murine keratinocytes (Aragane et al, 1997;Yoshimori et al, 1997). The immunosuppressive effect of gamma irradiation is also well known, but its mechanism has not been examined.…”
Section: Introductionmentioning
confidence: 99%